Psikologi Humanis; Mengurai Relasi Teoritik antara Psikologi dan Agama - Rangga Sa'adillah S.A.P.; Daiyatul Khusnah; Dewi Winarti (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2021)
Psychological discourse can be traced through the thoughts of Muslim philosophers such as Al-Kindi, Al-Farabi, Ibn Sina, and Al-Ghazali about the concept of the nafs. Its abstract but real structure forms the human psyche, received a warm welcome from Western thinkers such as Wilhelm Wundt and Ivan Pavlov so that psychology was born. Islamic teachings about psychology and psychology are not two different things but mutually support each other and complement each other, because in the development of psychology there are ups and downs in the relationship between psychology and religion. Through a multidisciplinary study of Islamic religious education, this article describes the terminology of Islamic psychology; human psychological elements; and the human driving force. At the end of this article, the author tries to find an estuary between western psychology and Islamic teachings on psychology which leads to humanist psychology. Humanist psychology is the latest period of the ebb and flow of the relationship between psychology and religion.